ANALISIS KINERJA OPERASIONAL KERETA API JURUSAN JAKARTA-PURWAKARTA (STUDI KASUS KERETA API WALAHAR EKSPRES DAN CILAMAYA EKSPRES) - Wisnu Adika; Prima Jiwa Osly (Universitas Trisakti, 2018)
This final project is an analysis of train operational performance analysis in Jakarta-Purwakarta department, case studies on the Walahar Ekspres and Cilamaya Ekspres trains. The method used to obtain primary data is observations or field surveys and questionnaires. Whereas for comparative data or secondary data obtained from PT. KAI (Daop) 1 Jakarta and from journals or other reference sources. The results of the analysis of the actual travel time of the average Walahar Ekspres train are 172 minutes. While the average actual travel time for the Cilamaya Ekspres train is 190 minutes. The actual downtime of the average Walahar Ekspres train is 37 minutes and the Cilamaya Ekspres train is 49 minutes. The highest train load factor. Walahar Ekspres is 96.38% and the lowest is 33.61%. The highest Cilamaya Ekspres fire train is 99.86% and the lowest is 28.61%. The comfort value of the carriage seat is 0.485 m 2 / spaced and the comfort of the seat is 0.194 m 2 / space. The level of passenger satisfaction on the Walahar Ekspres and Cilamaya Ekspres trains was satisfactory (an average of 72.18%).